Features of the Implementation of technological Solutions of the Bridge Crossing Construction Project with a Temporary Bridge - Ostapenko, I. S (Science and Transport Progress, 2022)
Purpose. The main aim of the research is the study of the methodology of conducting engineering and technical reconnaissance and the implementation of structural and technological solutions for the project of the construction of a bridge crossing with a temporary bridge damaged as a result of hostilities. Methodology. The achievement of the set goal involves research and analysis of practical structural and technological solutions for construction works, restoration of bridge crossings with temporary bridges, as well as study and generalization of practical experience of implemented technological solutions of combining wooden typical structures with steel typical span structures. Findings. A generalization of the experience of conducting engineering and technical reconnaissance in construction areas, restoration of bridge crossings in de-occupied territories was generalized. The author revealed and clarified the general key stages of the implementation of technological solutions for the project of the construction of a bridge crossing with a temporary bridge damaged as a result of hostilities using a combination of steel inventory bridge structures with wooden bridge structures. Originality. For the first time, the author investigated the peculiarities of conducting engineering and technical reconnaissance in order to implement the obtained results in the relevant project documentation for the construction of a temporary bridge. The peculiarities of constructive and technological solutions with a rational combination of various materials and structures during the construction of temporary bridges, which ensure a long period of their operation, are considered. Practical value. The elements of the methodology of organization and carrying out engineering technical exploration of terrain, water obstacles, construction sites and the base of logistics and other measures will contribute to the quality preparation of project documentation for the construction of bridge crossings with temporary bridges. The application peculiarities of non-standard projects of conducting works and structural and technological solutions in the construction of temporary bridges have a number of technological advantages that make it possible to ensure effective restoration of the destroyed combat actions of the bridges in a short time. Some technological methods of combinations of wooden structures and elements with steel carriers of the roadway when building temporary car bridges increase their load capacity.